Molecular techniques for pathogen identification and fungus detection in the environment - C.K.M. Tsui; J. Woodhall; W. Chen; C.A. Lévesque; A. Lau; C.D. Schoen; C. Baschien; M.J. Najafzadeh; G.S. de Hoog (IMA Fungus)
Many species of fungi can cause disease in plants, animals and humans. Accurate and robust detection and quantification of fungi is essential for diagnosis, modeling and surveillance. Also direct detection of fungi enables a deeper understanding of natural microbial communities, particularly as a great many fungi are difficult or impossible to cultivate. In the last decade, effective amplification platforms, probe development and various quantitative PCR technologies have revolutionized research on fungal detection and identification. Examples of the latest technology in fungal detection and differentiation are discussed here.